If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x = 8(x + 6) Reorder the terms: 8x = 8(6 + x) 8x = (6 * 8 + x * 8) 8x = (48 + 8x) Add '-8x' to each side of the equation. 8x + -8x = 48 + 8x + -8x Combine like terms: 8x + -8x = 0 0 = 48 + 8x + -8x Combine like terms: 8x + -8x = 0 0 = 48 + 0 0 = 48 Solving 0 = 48 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 12x-7=7x+3 | | [(-36)(-6)]= | | f(t)=0.25t^2-1.5t+2.5 | | a+13=19 | | -6/5= | | 7(x+8)=84 | | 7(x+9)+5=96 | | 6+5t^2=7t^2 | | 19+[-3+(-6)]= | | -7(x-3)=7 | | 1.8x-38=1.3x+8 | | 7x=x-4 | | 27x+30-77x=80 | | 4(3x-4)=19 | | 10n-15=65 | | -7(-1+3x)=-5(3-5x) | | 18x+6=21x+18 | | 67x+6-37x=9 | | 2x^2-23=.5 | | 2x-17=5x-23 | | Y=-3X^2-12X | | 8=5+v | | -7v=28 | | 15t-4=4-d | | 37=-7u+2(u-4) | | 2x^2=-12x-5 | | 3x-8=2x+23 | | 2x-8=3x-468 | | -4x+7=-10x+37 | | 213-3x=53 | | -4x+7=-10x | | 23=-8x-7+2x |